Contribution of Adversity Intelligence and Self-regulation to Student Accounting Learning Achievement - Auliya Damayanti (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The level of learning outcomes shown by students during the accounting learning process can be influenced by several factors, such as the adversity intelligence factor and the level of self-regulation each student possesses. This research aims to determine the contribution of adversity intelligence and self-regulation to the accounting learning achievement of class XI vocational school students. This research is classified as quantitative research with an ex post facto approach. The population in this study was all students in class. The data collection methods used in this research are questionnaire techniques and documentary techniques. The analysis method in this research uses simple/single regression, multiple regression, and partial correlation, which is processed using SPSS version 20. The results of this research show a positive contribution of 20.8%. So, there is a significant simultaneous contribution of adversity intelligence and self-regulation to accounting learning achievement. The higher the adversity intelligence and self-regulation, the higher the student's learning achievements.